Junie B. Jones and the Yucky Blucky Fruitcake - Park, Barbara; Brunkus, Denise (New York : Random House, 1999)
Junie, a spunky, sometimes exasperating, kindergartener, looks forward to winning lots of prizes at the school carnival, but a fruitcake was not exactly what she had in mind.
"A First Stepping Stone book."
3-6.
3-6.
Keywords: Behavior -- Fiction; Carnivals -- Fiction; Jones, Junie B. (Fictitious character) -- Fiction; Kindergarten -- Fiction; Schools -- Fiction; Carnivals -- Fiction; Human behavior -- Fiction; Jones, Junie B. (Fictional character) -- Fiction; Kindergarten -- Fiction; School stories